Determinant of service quality to Islamic banking customer satisfaction during Covid-19 - Hasyim, Fuad; Fauzi, Achmad Noor (Nur Science Institute, 2021)
Customer satisfaction is the key, where the company will survive because there is customer loyalty. This study aims to evaluate the effect of service quality (SERVQUAL) in measuring customer satisfaction in Islamic banking. The respondents of this study are Islamic banking customers in Surakarta. The sampling technique using convenience random sampling was obtained as many as 121 respondents. Data analysis used multiple linear regression with additional modifications of dummy variables to see the effect of the covid-19 pandemic on customer satisfaction. The results show that tangible, reliability, and empathy have a significant effect on customer satisfaction. Meanwhile, responsiveness and assurance variables have no significant effect on customer satisfaction. Other results found that the pandemic had no significant effect, meaning that Islamic banking continued to try to provide excellent service, whether in a pandemic or not.